Frequency of Fibroadenoma in Patients Presenting with Palpable Breast Lumps: A Cross-sectional Study: Fibroadenoma in Patients Presenting with Palpable Breast Lumps - Soomro, Saira Aijaz; Riaz, Yahya; Soomro, Dua Aijaz; Junejo, Afzal; Jabbar, Ahsan; Aijaz, Bushra (Pakistan Journal of Health Sciences, 2026)
Palpable breast lumps are a common presentation in surgical practice, particularly among young women, and encompass a wide range of benign and malignant conditions. Fibroadenoma is the most frequently encountered benign breast tumor in this age group; however, local hospital-based data on its frequency with statistical precision remain limited. Objectives: To estimate the proportion of fibroadenoma among female patients presenting with palpable breast lumps at a tertiary care hospital. Methods: This descriptive cross-sectional study was conducted at the Department of General Surgery, Bilawal Medical College, Liaquat University of Medical and Health Sciences (LUMHS), Hyderabad, from January 2025 to June 2025. A total of 60 female patients aged 15–35 years with clinically palpable breast lumps were enrolled using non-probability consecutive sampling. All patients underwent triple assessment, including clinical evaluation, imaging (ultrasound ± mammography), and Tru-Cut biopsy with histopathological examination. Data were analyzed using SPSS version 23.0. Frequencies were reported with 95% confidence intervals (CIs). Results: The mean age was 24.6 ± 4.8 years. Fibroadenoma was diagnosed in 22 patients, yielding a frequency of 36.7% (95% CI: 25.0–49.3%). The superolateral quadrant was the most commonly involved site. The proportion of fibroadenoma was consistent across age groups, BMI categories, marital status, breast laterality, and lump duration. Conclusions: Fibroadenoma constitutes over one-third of palpable breast lumps in young women presenting to a tertiary care hospital. These findings highlight the importance of structured diagnostic evaluation to guide appropriate management and avoid unnecessary surgical intervention.